Single and sequential biodegradable stent placement for refractory benign esophageal strictures: a prospective follow-up study - Hirdes, M. M. C.; Siersema, P. D.; van Boeckel, P. G. A.; Vleggaar, F. P. (Endoscopy, 2012)
Background and study aim: Although biodegradable stents do not require removal, a single biodegradable stent may only temporarily relieve dysphagia in patients with refractory benign esophageal stricture (RBES). The aim of this study was to evaluate the safety and long term efficacy of single and sequential biodegradable stent placement in patients with RBES.Patients and methods: All patients who underwent biodegradable stent placement for RBES between August 2008 and March 2011 were prospectively followed to evaluate recurrent dysphagia and complication rates. Results: In total, 59 stents were placed in 28 patients. Patients had previously been treated with multiple dilations (n = 20) or multiple dilations and non-biodegradable esophageal stenting (n = 8). A total of 13 patients underwent sequential biodegradable stent placement (median 3, range 2 – 8) during the study period. After initial stent placement, the median dysphagia-free period was 90 days (range 14 – 618 days). Clinical success (absence of dysphagia ≥ 6 months after stent placement) was achieved in seven patients (25 %) and major complications occurred in eight patients (29 %). After placement of a second biodegradable stent, the median dysphagia-free period was 55 days (range 25 – 700 days) and clinical success was achieved in 15 % of patients. After placement of a third stent, the median dysphagia-free period was 106 days (range 90 – 150 days), but none of the patients was clinically dysphagia-free.Conclusion: Placement of a single biodegradable stent is only temporarily effective in the vast majority of patients with RBES treated in a tertiary referral center. Sequential stenting may however be an option to avoid serial dilations.